Whole genome sequencing of the multidrug-resistant Chryseobacterium indologenes isolated from a patient in Brazil - Damas, Marcelo Silva Folhas; Ferreira, Roumayne Lopes; Campanini, Emeline Boni; Soares, Gabriela Guerrera; Campos, Leslie Camelo; Laprega, Pedro Mendes; Soares da Costa, Andrea; Freire, Caio César de Melo; Pitondo-Silva, André; Cerdeira, Louise Teixeira; Cunha, Anderson Ferreira da; Pranchevicius, Maria-Cristina da Silva (Frontiers in Medicine, 2022)
Chryseobacterium indologenes is a non-glucose-fermenting Gram-negative bacilli. This emerging multi-drug resistant opportunistic nosocomial pathogen can cause severe infections in neonates and immunocompromised patients. The aim of this study was to present the first detailed draft genome sequence of a multidrug-resistant C. indologenes strain, isolated from the cerebrospinal fluid of an infant hospitalized at the Neonatal Intensive Care Unit of Brazilian Tertiary Hospital. We first analyzed the susceptibility of C. indologenes strain to different antibiotics using the VITEK 2 system. The strain demonstrated an outstanding resistance to all antibiotic classes tested, including β-lactams; Aminoglycosides; Glycylcycline and Polymyxin. Next, C. indologenes was whole-genome-sequenced, annotated using Prokka and Rapid Annotation using Subsystems Technology (RAST), and screened for orthologous groups (EggNOG), gene ontology (GO), resistance genes, virulence genes, and mobile genetic elements using different software tools. The draft genome contained one circular chromosome of 4,836,765 bp with 37.32% GC content. The genomic features of chromosome present numerous genes related to cellular processes that are essential to bacteria. The MDR C. indologenes revealed the presence of genes which corresponded to the resistance phenotypes, including genes to β-lactamases (blaIND-13, blaCIA-3, blaTEM-116, blaOXA-209, blaVEB-15), quinolone (mcbG), tigecycline (tet(X6)), and genes encoding efflux pumps which confer resistance to aminoglycosides (RanA/RanB), and colistin (HlyD/TolC). Amino acid substitutions related with quinolone resistance were observed in GyrA (S83T) and GyrB (L425I and K473R). A mutation that may play a role in the development of colistin resistance was detected in lpxA (G68D). Chryseobacterium indologenes isolate harboured 19 virulence factors, most of them involved in infection pathways. We identified 13 Genomic Islands (GIs) and some elements associated to one integrative and conjugative element (ICEs). Other elements linked to Mobile Genetic Elements (MGEs) such as insertion sequence (ISEIsp1), transposon (Tn5393), and integron (In31) were also present in the C. indologenes genome. Although plasmids were not detected, a ColRNAI replicon type and most resistance genes detected in singletons were identified in unaligned scaffolds. We provided a wide range of information towards understanding of the genomic diversity of C. indologenes, which can contribute to control the evolution and dissemination of this pathogen in healthcare settings.